MISKOLC - SATORALJAUJHELY - ΒΟΥΔΑΠΕΣΤΗ: ΑΝΑΖΗΤΩΝΤΑΣ ΤΑ ΙΧΝΗ ΤΗΣ ΕΛΛΗΝΙΚΗΣ ΕΜΠΟΡΙΚΗΣ ΔΙΑΣΠΟΡΑΣ ΣΤΗΝ ΟΥΓΓΑΡΙΑ - ΜΑΝΤΟΥΒΑΛΟΣ, ΙΚΑΡΟΣ (Eoa kai Esperia, 2007)
The dual character of the trade diaspora of the Greeks is substantiated onthe one hand by the way they organized themselves and functioned within theHungarian bourgeois environment and, on the other, by the social andeconomic structures of the regions where they settled. The different historicalmanifestations of the activity of the Greeks are reflected in the archivallocations themselves: in the archive of the Greek Orthodox community ofMiskolc and the municipal archive of Sâtoraljaujhely, which came under theMunicipal Archive of Miskolc (Borsod - Abauj - Zemplén Megyei Levéltâr).The first comprises ledgers, account books, church and school registers, aswell as a mass of loose documents of diverse content, dating back to the early18th up to the mid-19th century, written mostly in the Greek language.Conversely, at the Sâtoraljaujhely archive, the lack of a separate archivalclassification for the Greeks can only be interpreted as proof of the swiftassimilation of the trade immigrants into the social and economic fabric of thehost city. Documents in Latin and Hungarian scattered within the archivalunities take on a special meaning in terms of the depth of the historicalresearch and the examination of individual events, which are interwoven withthe presence of Greek merchants in the province of Zemplén, in northeasternHungary. The tracing of the Greek presence in Hungary is completed by a visit tothe Budapest Public Archive. Testaments and inheritance inventoriesbelonging to members of the Greek and Macedonian-Vlach communities ofPest were selected and photocopied. Aspects of private lives, the hierarchy ofrelationships, intertribal roles, the composition and structure of thehouseholds, as well as strategies for the transfer of property are cast in highrelief through the microhistorical examination of the material, illustrating themindset and perceptions that governed people's behaviour in the real world.